Persistence of Immune Responses Through 36 Months in Healthy Adults After Vaccination With a Novel Staphylococcus aureus 4-Antigen Vaccine (SA4Ag). (24th December 2019) - Creech, C Buddy; Frenck, Robert W; Fiquet, Anne; Feldman, Robert; Kankam, Martin K; Pathirana, Sudam; Baber, James; Radley, David; Cooper, David; Eiden, Joseph; Gruber, William C; Jansen, Kathrin U; et al.
Abstract: Background: Staphylococcus aureus causes serious health care– and community-associated disease, requiring improved preventive measures such as vaccines. The investigational S. aureus 4-antigen vaccine (SA4Ag), comprising capsular polysaccharide serotypes 5 and 8 (CP5 and CP8) conjugated to CRM197, recombinant mutant clumping factor A (r m ClfA), and recombinant manganese transporter protein C (rP305A or rMntC), was well tolerated, inducing robust functional immune responses to all 4 antigens through 12 months postvaccination. This is a serological extension study through 36 months postvaccination. Methods: In 2 previous studies, healthy adults received SA4Ag, SA3Ag (without rMntC), or placebo; serology was also assessed at ~24 and ~36 months postvaccination. Functional immune responses (antibody responses that facilitate killing of S. aureus or neutralize S. aureus virulence mechanisms) were assessed with opsonophagocytic activity killing assays (CP5 or CP8) and a fibrinogen-binding inhibition assay (ClfA). A competitive Luminex immunoassay assessed ClfA and rMntC responses. Adverse events within 48 hours of blood draw were recorded. Results: Four hundred forty subjects (18–64 years old, 255; 65–85 years old, 185) were enrolled. At 24 and 36 months postvaccination, subjects receiving SA4Ag had substantially higher geometric mean titers (GMTs) for CP5, CP8, and ClfA vs baseline; geometric mean fold rises (GMFRs) from baseline to month 36 were 2.7–8.1. For rMntC, 36-month GMTs declined from peak levels but remained above baseline for all SA4Ag groups; GMFRs from baseline to month 36 were 1.8 and 1.5 in the younger and older cohorts, respectively. Conclusions: Persistent functional immune responses to S. aureus antigens were observed through 36 months in healthy adults. ClinicalTrials.gov: NCT01643941 and NCT01364571.